PERFORMANCE OF STRAIGHTBRED FRIESIAN AND CHAROLAIS X FRIESIAN CROSSBRED MALES SLAUGHTERED AT THREE DIFFERENT AGES - Nigm, A.A.; Alhadrami, G.A.; Kholif, A.M.; Abulla, O.M. (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text